Effect of ball milling process on microstructure and mechanical properties of CNTs/Al composites - YOU Yuanqi; LI Caiju; YANG Chao; XING Yuan; PENG Yanzhi; YI Jianhong (Fenmo yejin jishu)
Carbon nanotubes (CNTs) and aluminum composite powders were prepared by both wet ball milling and dry ball milling. The CNTs reinforced aluminum matrix (CNTs/Al) composites were fabricated by sparking plasma sintering (SPS) combined with hot extrusion process, and the relationship of preparation process, microstructure, and mechanical properties was explored systematically. The results show that, compared with the dry ball milling, the wet ball milling can better disperse CNTs, and significantly reduce the damage to the structure of CNTs. The ethanol ball milling medium has the cooling effect to significantly refine the grain size and reduce the cold welding of the powders, resulting in the excellent mechanical properties of the composites. The tensile strength of 2%CNTs/Al composites sintered and hot extruded after wet ball milling for 6 h reaches 207 MPa.